Activity of Minocycline Against Acinetobacter calcoaceticus Var. anitratus (Syn. Herellea vaginicola) and Serratia Marcescens - Maderazo, Eufronio G. (1975)
The activity of minocycline and tetracycline against 23 isolates of Acinetobacter calcoaceticus var. anitratus (syn. Herellea vaginicola) and 178 strains of Serratia marcescens was determined by disk and microdilution methods. The results indicate that minocycline is highly active against this species of Acinetobacter, all but one strain being inhibited by 0.007 μg of the antibiotic per ml. Tetracycline was also active, though to a lesser degree, against A. calcoaceticus. Of the 178 strains of S. marcescens tested, only seven (3.9%) had a minimum inhibitory concentration of 2 μg or less of minocycline per ml. Tetracycline was less active than minocycline against S. marcescens; with 2 μg of tetracycline per ml, only 2 of 152 (1.3%) strains were inhibited. At concentrations of 8 and 16 μg of minocycline per ml, which can be achieved in the urine with the usual doses, 44.9 and 63.5% of S. marcescens strains were inhibited, which implies its possible usefulness for the therapy of urinary tract infection due to this organism.